Attenuation of Pseudomonas aeruginosa quorum sensing, virulence and biofilm formation by extracts of Andrographis paniculata. (December 2017) - Banerjee, Malabika; Moulick, Soumitra; Bhattacharya, Kunal Kumar; Parai, Debaprasad; Chattopadhyay, Subrata; Mukherjee, Samir Kumar
Abstract: Quorum-sensing (QS) is known to play an essential role in regulation of virulence factors and toxins during Pseudomonas aeruginosa infection which may frequently cause antibiotic resistance and hostile outcomes of inflammatory injury. Therefore, it is an urgent need to search for a novel agent with low risk of resistance development that can target QS and inflammatory damage prevention as well. Andrographis paniculata, a herbaceous plant under the family Acanthaceae, native to Asian countries and also cultivated in Scandinavia and some parts of Europe, has a strong traditional usage with its known antibacterial, anti-inflammatory, antipyretic, antiviral and antioxidant properties. In this study, three different solvent extracts ( viz ., chloroform, methanol and aqueous) of A. paniculata were examined for their anti-QS and anti-inflammatory activities. Study was carried out to assess the effect on some selected QS-regulatory genes at transcriptional level using Real Time-PCR. In addition, ability to attenuate MAPK pathways upon P. aeruginosa infection was performed to check its potential anti-inflammatory activity. Chloroform and methanol extracts showed significant reduction ( p  < 0.05) of the QS-controlled extracellular virulence factors in P. aeruginosa including the expression of pyocyanin, elastase, total protease, rhamnolipid and hemolysin without affecting bacterial viability. They also significantly ( p  < 0.05) reduced swarming motility and biofilm formation of P. aeruginosa . The chloroform extract, which was found to be more effective, decreased expression of lasI, lasR, rhlI and rhlR by 61%, 75%, 41%, and 44%, respectively. Moreover, chloroform extract decreased activation of p-p38 and p-ERK1/2 expression levels in MAPK signal pathways in P. aeruginosa infected macrophage cells. As the present study demonstrates that A. paniculata extracts inhibit QS in P. aeruginosa and exhibit anti-inflammatory activities, therefore it represents itself as a prospective therapeutic agent against P. aeruginosa infection. Graphical abstract: Highlights: Anti-QS action of Andrographis paniculata extracts against P. aeruginosa PAO1. It reduced expression of pyocyanin, elastase, protease, rhamnolipid and hemolysin. It affected swarming motility and biofilm formation of P. aeruginosa. A. paniculata chloroform extract decreased expression of lasI, lasR, rhlI and rhlR. Also reduced p-p38 and p -ERK expression in P. aeruginosa infected macrophage cells.